2006
DOI: 10.2337/db05-1360
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glucose Tolerance and Hepatic Insulin Sensitivity by Oligofructose Requires a Functional Glucagon-Like Peptide 1 Receptor

Abstract: Nondigestible fermentable dietary fibers such as oligofructose (OFS) exert an antidiabetic effect and increase the secretion of glucagon-like peptide 1 (GLP-1). To determine the importance of GLP-1 receptor-dependent mechanisms for the actions of OFS, we studied high-fat-fed diabetic mice treated with OFS for 4 weeks in the presence or absence of the GLP-1 receptor antagonist exendin 9-39 (Ex-9). OFS improved glucose tolerance, fasting blood glucose, glucose-stimulated insulin secretion, and insulinsensitive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
328
2
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(368 citation statements)
references
References 47 publications
(43 reference statements)
24
328
2
12
Order By: Relevance
“…According to these results, we have previously shown that HF-diet-induced hepatic insulin resistance was normalised in OFS fed mice, without significant improvement in whole-body insulin sensitivity [18]. Moreover, the improved hepatic insulin sensitivity observed in HF-OFS fed mice was strongly associated with a significantly lower hepatic inflammatory tone [18]. Since we observed higher endotoxaemia in HF-diet-fed mice, we measured plasma and adipose tissue inflammatory markers.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…According to these results, we have previously shown that HF-diet-induced hepatic insulin resistance was normalised in OFS fed mice, without significant improvement in whole-body insulin sensitivity [18]. Moreover, the improved hepatic insulin sensitivity observed in HF-OFS fed mice was strongly associated with a significantly lower hepatic inflammatory tone [18]. Since we observed higher endotoxaemia in HF-diet-fed mice, we measured plasma and adipose tissue inflammatory markers.…”
Section: Discussionmentioning
confidence: 51%
“…Diet and experimental groups Mice (n=8 per group) were fed four different experimental diets for 14 weeks as follows: (1) standard diet (control) (A04; UAR, Villemoisson-sur-Orge, France) [17]; (2) HF diet containing 49.5% fat (g/100 g of total dry diet) corresponding to 72% of the total energy content (UAR, Epinay-sur-Orge, France); (3) a mix of HF diet and a fermentable dietary fibre (OFS) (HF-OFS) (kind gift from Orafti, Tienen, Belgium) [18]; and (4) a mix of HF diet and a non-fermentable dietary fibre (microcrystalline cellulose [HF-Cell]) (Vivapur microcrystalline cellulose; J. Rettenmaier & Söhne, Weissenborn, Germany). Dietary fibre was added in a proportion of 90:10 (weight of HF diet:weight of fibre).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An oral glucose tolerance test was performed 7 weeks after the beginning of the feeding period [7,28,29]. Six-hour-fasted mice received an oral load of glucose (Fluka, Buchs, Switzerland) of 3 g/kg body wt with a 660 g/l glucose solution.…”
Section: Oral Glucose Tolerance Testmentioning
confidence: 99%
“…Des arguments expérimen-taux d'une autre nature suggèrent que la fermentation de glucides non digestibles n'augmente pas la masse grasse, mais, au contraire, contribue à réduire les altérations métaboliques associées à l'obésité. Ainsi, notre équipe et d'autres auteurs ont montré qu'une alimentation riche en fibres « fermentescibles » non digestibles (fructanes) diminuait le poids corporel, le développement de la masse adipeuse et la sévérité du diabète dans plusieurs modèles animaux [15][16][17][18][19]. Ces fibres alimentaires sont totalement fermentées dans le côlon, permettant aux bactéries utilisant préférentiellement ces composés comme source énergétique -en l'occurrence les bifidobactéries -de se développer.…”
Section: Extraction Et Absorption De L'énergie Non Digéréeunclassified